The Role of Androgen Receptor in Cross Talk Between Stromal Cells and Prostate Cancer Epithelial Cells - Tang, Qianyao; Cheng, Bo; Dai, Rongyang; Wang, Ronghao (Frontiers in Cell and Developmental Biology, 2021)
Prostate cancer (PCa) lists as the second lethal cancer for men in western countries and androgen receptor (AR) plays central role in its initiation and progression, which prompts the development of androgen deprivation therapy (ADT) as the standard treatment. In addition, tumor microenvironment, consisting of stromal cells and extracellular matrix, has a dynamic communication with PCa epithelial cells and supports their growth. Importantly, ADT treatment enhances this reciprocal interaction and predisposes stromal cells to promote cell invasion of PCa cells. During this process, AR actively responds to various stimuli derived from the surrounding stromal cells and undergoes degradation, elevating expression levels of certain genes responsible for cell invasion. AR reduction also accelerates PCa cells to differentiate into cancer stem like cells and neuroendocrine cells. Overall, understanding of the cross-talks between tumor microenvironment and PCa at the molecular level may assist the development of novel therapeutic strategies against this type of disease. This review will provide a snapshot of AR’s action when the interaction of stromal cells and PCa cell occurs.